Does Blended Learning Method Impact on Critical Ability? - Faslah, Roni; Saptono, Ari; Wibowo, Agus; Suparno; Kandy, Pinky; Febriantina, Susan; Rahmaningtyas, Wisudani (International Journal of Psychosocial Rehabilitation, 2020)
This study reveals how the Blended Learning Method can improve students' critical thinking skills. The ease of use of information technology, if not balanced with specific skills in managing learning by the teacher, makes students trapped in surfing to find information. This condition will make students not optimal in exploring analytic thinking; the level of plagiarism increases, and students tend to spoiled with technology. For this reason, the authors investigate the blended learning method used by teachers in the learning process by using quiz forms in improving analytical thinking skills. The results of this study indicate that: 1) There are differences in critical thinking skills between students who use the blended learning method and conventional methods, 2) There are differences in critical thinking skills between students who are given essay and multiple choice quiz forms, 3) There is an interaction between learning methods and forms of quiz on critical thinking skills, 4) There are differences in students 'critical thinking abilities given the form of essay quiz in the blended learning method and conventional methods, 5) There are differences in students' critical thinking skills which are given a multiple choice quiz form on the blended learning method and conventional methods, 6) There are differences in students 'critical thinking skills using the method blended learning by providing essay and multiple choice quiz forms, 7) There are differences in students' critical thinking skills using conventional methods by providing essay test and multiple-choice forms.